Comprehensive investigations on anti-leishmanial potentials of Euphorbia wallichii root extract and its effects on membrane permeability and apoptosis. (June 2019) - Ahmad, Bilal; Islam, Arshad; Khan, Arif; Khan, Mubarak Ali; ul Haq, Ihsan; Jafri, Laila; Ahmad, Mansoor; Mehwish, Shaila; Khan, Ajmal; Ullah, Nazif
Highlights: Euphorbia wallichii carry high antileishmanial potentials. Euphorbia wallichii kills Leishmania cells via membrane permeability and apoptosis. Euphorbia wallichii carry low cytotoxicity to human blood erythrocytes. Abstract: Clinically available synthetic chemotherapeutics to treat the vector-borne protozoan infection, leishmaniasis, are associated with serious complications such as toxicity and emergence of resistance. Natural products from plants consist of interesting biomolecules that may interfere with DNA or membrane integrity of the parasite and can possibly minimise the associated side effects. In the present study, various fractions of Euphorbia wallichii (EW) root extracts including n-hexane (EWNX), ethyl acetate (EWEA), chloroform (EWCH) and aqueous (EWAQ), were evaluated for their antileishmanial potential against Leishmania tropica followed by investigation of the possible mechanism of action via reactive oxygen species (ROS) quantification, membrane permeability (via sytox green dye) and apoptotic assay (via AO/EB method) using fluorescent microscopy. Two of the fractions i.e. EWEA and EWAQ inhibited the growth of promastigotes (IC50 7.8 and 10.2 μg/mL, respectively) and amastigotes (IC50 9.9 and 13.3 μg/mL, respectively) forms almost at similar concentrations as found for the standard antileishmanial drugs, tartar emetic (TA) and Glucantime (IC50 9.4 and 21.5 μg/mL, respectively). Both the active fractions remained non-toxic towards human blood erythrocytes and were able to cause membrane permeability and apoptotic induction (using Triton X-100 as a positive control) leading to death of Leishmania parasites. However, both the fractions could not triger significant and persistent ROS generation, compared to hydrogen peroxide used as a positive control. Antilesihmanial activity of the two active fractions might be attributed to the presence of high quantity of tannins and saponins.